Government Policy on the Provision of Certificate of Ownership Rights : A Strategic Step for Legal Protection of the Community - Putri Amaliah Baderung; Fence M. Wantu; Nur Mohamad Kasim (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Since 2017, the Ministry of Agrarian Affairs and Spatial Planning/Head of the National Land Agency has been tasked by President Joko Widodo to complete land registration across Indonesia by 2025 through the Complete Systematic Land Registration Program (PTSL). Based on Ministerial Regulation ATR/BPN Number 12 of 2017, updated with Number 6 of 2018, this program aims to provide legal certainty and protection of land rights for the community. However, many people, especially in North Gorontalo Regency, still do not understand how to obtain land certificates due to a lack of information and education about PTSL. This research aims to explore government policies that provide land ownership certificates as legal protection for the community. Better coordination is needed between local governments and the Ministry of ATR/BPN to raise public awareness of the importance of land certificates, which not only guarantee ownership but can also be utilized as business capital. The PTSL program is expected to improve community welfare and reduce land disputes. Research findings indicate that public understanding in North Gorontalo Regency remains low, with obstacles such as a lack of information, complicated procedures, and limited access. Government policies need to include regulatory simplification and increased transparency as well as public services.